Social Media, Brand Image, and Price: Influencing Cryptocurrency Purchasing on Tokocrypto: Pengaruh Media Sosial, Citra Merek, dan Harga terhadap Keputusan Pembelian Konsumen Cryptocurrency: Studi Kuantitatif pada Aplikasi Tokocrypto - Fajar Fakhrur Fiqri; Mas Oetarjo (Academia Open, 2023)
This research study investigates the influence of social media, brand image, and price on cryptocurrency consumer purchasing decisions within the context of Tokocrypto applications. The study employs a quantitative approach, utilizing a non-probability sampling method with purposive sampling techniques to gather data from 100 respondents through online questionnaires distributed via Google Forms. The collected data is analyzed using multiple linear regression through the SPSS Statistics program (version 18). The results reveal significant relationships between social media, brand image, and price with purchasing decisions. Specifically, social media and brand image positively impact purchasing decisions, while price exerts a negative influence. Furthermore, when considered together, social media, brand image, and price collectively affect consumer purchasing decisions. These findings provide valuable insights for businesses operating in the cryptocurrency market, enabling them to devise effective marketing strategies and enhance customer engagement to drive purchasing decisions. Highlights: The study examines the influence of social media, brand image, and price on cryptocurrency consumer purchasing decisions. Quantitative methods are utilized, with a sample of 100 respondents and data collected through online questionnaires. The results demonstrate the significant impact of social media, brand image, and price on consumer purchasing decisions in the context of Tokocrypto applications. Keywords: Social Media, Brand Image, Price, Cryptocurrency, Purchasing Decisions.